Communication Impairment in Ultrasonic Vocal Repertoire during the Suckling Period of Cd157 Knockout Mice: Transient Improvement by Oxytocin - Lopatina, Olga L.; Furuhara, Kazumi; Ishihara, Katsuhiko; Salmina, Alla B.; Higashida, Haruhiro (Frontiers in Neuroscience, 2017)
Communication consists of social interaction, recognition, and information transmission. Communication ability is the most affected component in children with autism spectrum disorder (ASD). Recently, we reported that the CD157/BST1 gene is associated with ASD, and that CD157 knockout (Cd157−/−) mice display severe impairments in social behavior that are improved by oxytocin (OXT) treatment. Here, we sought to determine whether Cd157−/− mice can be used as a suitable model for communication deficits by measuring ultrasonic vocalizations (USVs), especially in the early developmental stage. Call number produced in pups due to isolation from dams was higher at postnatal day (PND) 3 in knockout pups than wild-type mice, but was lower at PNDs 7 and 10. Pups of both genotypes vocalized with a poorer voice repertoire at PND 3. However, although wild-type pups emitted USVs consisting of six different syllable types at PNDs 7 and 10, knockout pups vocalized with only two types. This developmental impairment in USV emission was rescued within 30 min by intraperitoneal OXT treatment, but quickly returned to control levels after 120 min, showing a transient effect of OXT. USV impairment was partially observed in Cd157+/- heterozygous mice, but not in Cd157−/− adult male mice examined while under courtship. These results demonstrate that CD157 gene deletion results in social communication insufficiencies, and suggests that CD157 is likely involved in acoustic communication. This unique OXT-sensitive developmental delay in Cd157−/− pups may be a useful model of communicative interaction impairment in ASD.